Search for supersymmetry in pp collisions at √s = 7 TeV in events with a single lepton, jets, and missing transverse momentum - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Erö, J.; Fabjan, C.; Friedl, M.; Frühwirth, R.; Ghete, V. M.; et al. (My University, 2011)
Results are reported from a search for physics beyond the standard model in proton-proton collisions at a center-of-mass energy of 7TeV, focusing on the signature with a single, isolated, high-transverse-momentum lepton (electron or muon), energetic jets, and large missing transverse momentum. The data sample comprises an integrated luminosity of 36 pb-1, recorded by the CMS experiment at the LHC. The search is motivated by models of new physics, including supersymmetry. The observed event yields are consistent with standard model backgrounds predicted using control samples obtained from the data. The characteristics of the event sample are consistent with those expected for the production of tt̄ and W+jets events. The results are interpreted in terms of limits on the parameter space for the constrained minimal supersymmetric extension of the standard model.
Keywords: Hadron-hadron scattering